Human Metapneumovirus-Induced Host microRNA Expression Impairs the Interferon Response in Macrophages and Epithelial Cells - Iván Martínez-Espinoza; Anang D. Bungwon; Antonieta Guerrero-Plata (Viruses, 2023)
Human metapneumovirus (HMPV) is a nonsegmented, single-stranded negative RNA virus and a member of the Pneumoviridae family. During HMPV infection, macrophages play a critical role in defending the respiratory epithelium by secreting large amounts of type I interferon (IFN). MicroRNAs (miRNAs) are small, noncoding, single-stranded RNAs that play an essential role in regulating gene expression during normal cellular homeostasis and disease by binding to specific mRNAs, thereby regulating at the transcriptional and post-transcriptional levels with a direct impact on the immune response and other cellular processes. However, the role of miRNAs in macrophages and respiratory viral infections remains largely unknown. Here, we characterized the susceptibility of THP-1-derived macrophages to HMPV infection and the effect of hsa-miR-4634 on these cells. Transfection of an miRNA mimic and inhibitor demonstrated that hsa-miR-4634 regulates the IFN response in HMPV-infected macrophages, suggesting that HMPV induces the expression of the miRNA as a subversion mechanism of the antiviral response. This effect was not limited to macrophages, as a similar effect was also observed in epithelial cells. Overall, our results demonstrate that hsa-miR-4634 is an important factor in regulating the IFN response in macrophages and epithelial cells during HMPV infection.